Research, Innovation and Development on Corylus avellana through the Bibliometric Approach. (21st September 2020) - Raparelli, Elisabetta; Lolletti, Daniele
ABSTRACT: Among the dried fruits, hazelnut cultivation represents one of the greater world productions. Based on this consideration, it has been decided to verify whether the great commercial importance of this fruit corresponds to an equally dynamic and productive scientific activity. The aim of this study is to analyze the network structure and the conceptual evolution of research on Corylus avellana through time. A scientific mapping approach was used and applied to a set of scientific publications from 1980 to 2019, retrieved from the Scopus database. From this period, the Scopus search provided 861 documents. During the 1980–1999 period, research topics were poorly characterized, but better defined in the 2000–2019 period. From 2000 to 2009, the research focused on three distinct areas of interest: (i) genetic techniques aimed at the study and resolution of phytosanitary problems; (ii) genetic improvement of new cultivars in order to obtain production quality; (iii) open-field cultivation techniques to improve the quantity of hazelnut production and the quality of the product. In the last decade (2010–2019), genetic improvement techniques, both in the laboratory and in the field, have merged into a single cluster using the most innovative molecular biology techniques. At the same time, the cultivation techniques were oriented not only toward production in the field, but also at studying and improving the quality of the products. Through the analysis was possible to trace some future lines of scientific research for this relatively unexplored topic.